2022
DOI: 10.1002/jcp.30721
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response signaling pathways as important targets for combination therapy and chemotherapy sensitization in osteosarcoma

Abstract: Osteosarcoma (OS) is the most common bone malignancy that occurs most often in young adults, and adolescents with a survival rate of 20% in its advanced stages. Nowadays, increasing the effectiveness of common treatments used in OS has become one of the main problems for clinicians due to cancer cells becoming resistant to chemotherapy. One of the most important mechanisms of resistance to chemotherapy is through increasing the ability of DNA repair because most chemotherapy drugs damage the DNA of cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…MDR remains a significant obstacle to successful chemotherapy treatment for osteosarcoma patients . One of the most important mechanisms by which osteosarcoma remained resistant to radiotherapy or chemotherapy is an increase in the ability of intracellular DNA damage response (DDR). , DDR is a signal transduction pathway involved in protecting cells against DNA damage caused by endogenous and exogenous factors such as chemotherapy agents, ionizing radiation (IR), and replication fork stress. , Previous studies have demonstrated that Nrf-2 plays an important role in DDR against DNA damage via numerous mechanisms such as the antioxidant and ATR pathways, as demonstrated in Figure D. Considering the good targeting properties, excellent ROS generation ability, and significant Nrf2 inhibition effect of FDPM nanoparticles, we hypothesized that the efficiency of radiotherapy could be significantly improved by FDPM nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDR remains a significant obstacle to successful chemotherapy treatment for osteosarcoma patients . One of the most important mechanisms by which osteosarcoma remained resistant to radiotherapy or chemotherapy is an increase in the ability of intracellular DNA damage response (DDR). , DDR is a signal transduction pathway involved in protecting cells against DNA damage caused by endogenous and exogenous factors such as chemotherapy agents, ionizing radiation (IR), and replication fork stress. , Previous studies have demonstrated that Nrf-2 plays an important role in DDR against DNA damage via numerous mechanisms such as the antioxidant and ATR pathways, as demonstrated in Figure D. Considering the good targeting properties, excellent ROS generation ability, and significant Nrf2 inhibition effect of FDPM nanoparticles, we hypothesized that the efficiency of radiotherapy could be significantly improved by FDPM nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…3 One of the most important mechanisms by which osteosarcoma remained resistant to radiotherapy or chemotherapy is an increase in the ability of intracellular DNA damage response (DDR). 51,52 DDR is a signal transduction pathway involved in protecting cells against DNA damage caused by endogenous and exogenous factors such as chemotherapy agents, ionizing radiation (IR), and replication fork stress. 53,54 Previous studies have demonstrated that Nrf-2 plays an important role in DDR against DNA damage via numerous mechanisms such as the antioxidant and ATR pathways, 54−56 as demonstrated in Figure 3D.…”
Section: Effects Of Fe 3 O 4 Nanoparticles On Oxidative Homeostasis I...mentioning
confidence: 99%
“…A better understanding of the relationship between OS glucose metabolism processes and signaling pathways will help optimize the treatment strategy of OS. In addition, JNK pathway [144] , Notch pathway [145] , Fas/FasL signaling pathway [146] , Hedgehog signaling pathway [147] , DNA damage response signaling pathway [148] , VEGF signaling pathway [149] and other cell signaling pathways are closely related to the progression of OS. However, the relationship between the above signaling pathways and OS cell glucose metabolism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with osteosarcoma, most current treatment programs usually involve intensive neoadjuvant chemotherapy [ 27 ]. However, chemotherapy resistance is an important factor affecting the disease progression and survival of patients with osteosarcoma [ 28 ]. Our study shows that EBLN3P can affect the MTX resistance of osteosarcoma cells by regulating miR-200a-3p, an important microRNA that affects EMT.…”
Section: Discussionmentioning
confidence: 99%